First detection of Culex tritaeniorhynchus in Western Australia using molecular diagnostics and morphological identification - Kimberly L. Evasco; Craig Brockway; Tamara Falkingham; Margaret Hall; Nerida G. Wilson; Abbey Potter (Parasites & Vectors)
Abstract Background Culex tritaeniorhynchus has long been considered the primary vector of Japanese encephalitis virus (JEV), but until recently, it was considered exotic to Australia. When the species was detected in the country’s Northern Territory (NT) for the first time, the Western Australia (WA) Department of Health was cognisant of the risk it posed to the State because of the shared border and continuous mosquito habitat adjoining the two jurisdictions. The aim of this study was to undertake intensive mosquito surveillance in the Kimberley region to ascertain whether Cx. tritaeniorhynchus was present in WA, define the extent of its distribution and undertake phylogenetic analysis of select specimens to support hypothesized routes of entry into the state. Methods Carbon dioxide (CO2)-baited encephalitis virus surveillance (EVS) mosquito traps were deployed at various sites throughout the Kimberley region by surveillance officers within the Medical Entomology unit of the Western Australia (WA) Department of Health. Mosquitoes were then morphologically identified, and a subset of four specimens were confirmed as Cx. tritaeniorhynchus by molecular identification using Cytochrome Oxidase I (COI) DNA data and phylogenetic analysis. Results From 31 March 2021 to 30 May 2024, a total of 211 female Cx. tritaeniorhynchus specimens were collected from 21 unique trap sites in the Kimberley’s Shire of Wyndham-East Kimberley (SWEK). Four COI DNA barcode regions were amplified and successfully sequenced for analysis. These sequences fell within a clade recognised as Cx. tritaeniorhynchus and specifically all sequences were in a clade with other specimens from the NT and Timor-Leste. Conclusions This study represents the first detection of Cx. tritaeniorhynchus in WA. Given the widespread nature of trap sites that yielded the species and consecutive seasons over which it was observed, the authors surmise that Cx. tritaeniorhynchus is now established within the northeast Kimberley region. The findings are significant given the detection of the species coincides with the first significant outbreak of JEV activity on mainland Australia involving an estimated 45 human cases of Japanese encephalitis, 80 impacted commercial piggeries and widespread feral pig activity. Although the role that Cx. tritaeniorhynchus may play in JEV transmission into the future is not yet understood, it presents a potential risk to public health in the region. Graphical abstract